Mycobacterial isolations in young adults with cystic fibrosis. Issue 5 (May 1984) - Smith, M J; Efthimiou, J; Hodson, M E; Batten, J C
Abstract : In 223 patients admitted to hospital with cystic fibrosis mycobacteria were found in the sputa of seven. All of these cases were identified over a six year period after the introduction of routine examination and culture of sputum for acid fast bacilli in patients with cystic fibrosis. The organisms isolated were Mycobacterium tuberculosis in three patients, M chelonei in one, M fortuitum in one, and unidentified mycobacteria in two. The diagnosis was not suspected on clinical grounds in any of the cases; in one patient, however, night sweats were a prominent feature before diagnosis. In four of the patients direct sputum smear examination did not reveal the organism, which was grown subsequently in culture. An unusual phenomenon of liquefaction of the Lowenstein-Jensen culture medium was encountered in five of the seven patients described, which in one case made identification and sensitivity testing of the organism impossible. This phenomenon has been observed in sputum cultures from other patients with cystic fibrosis but not in other pulmonary diseases. Immunological studies performed in three of the patients showed normal numbers of peripheral blood T and B lymphocyte in all three; in vitro lymphocyte transformation to tuberculin PPD was, however, reduced in the patient with extensive M fortuitum infection, which proved fatal. Mycobacteria may be present in the sputa of patients with cystic fibrosis more often than previously recognised and therefore sputum examination and culture for mycobacteria should be performed periodically in these patients.